Pengaruh Pelatihan Teknis dan Disiplin Kerja Terhadap Kinerja Pegawai di Sekretariat Utama Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) - Annisa Fadhila; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research is aimed to know if there are any influences between technical training and work discipline on employee performance at the General Secretariat of the Financial Transaction Reports and Analysis Center (INTRAC). This Research uses quantitative methods by conducting surveys and testing to 52 employee in the general secretariat. The sampling method is non-probability sampling. Data was collected by distributing questionnaires using a Likert scale to measure each statement, the tests carried out were validity tests, reliability tests, classical assumption tests, hypothesis tests, and multiple regression tests with the help of the IBM SPSS Statistics 20 program. The results showed that the technical training variable have a significant effect on employee performance, work discipline variables significantly affect employee performance, and technical training and work discipline variables have a significant effect on employee performance.